Improvement of stress adaptation and insulin resistance in women with GDM by WeChat group management during novel coronavirus pneumonia - Feng, Yan; Lv, Yuping; Feng, Qi; Song, Xinna; Li, Xiaoyan; Wang, Yongjun (Frontiers in Nutrition, 2023)
Aim: To evaluated the improvement of glycemic control and stress adaptation in GDM patients by mobile phone WeChat management during novel coronavirus pneumonia. Mehods: 75 GDM women were included in this study, 35 women were included in mobile wechat group management as GDM-M group, and 40 women as GDM group. Results: After mobile wechant group management for 4 weeeks, E and NE were lower. MDA was lower and SOD was highe. HOMA-IR was lower. E, NE and cortisol were related to HOMA-IR positively, MDA was positively and SOD was negatively related to HOMA-IR. E and cortisol were related to MDA positively, and were negatively related to SOD. Conclusion: GDM patients who have complete mobile wechat group management can improve stress adaptation disorder and insulin resistance during novel coronavirus pneumonia. Mobile wechant management played a positive role in improving inulin resistance of GDM women under special circumstances, which may reduce the risk of complications in maternal and fetal.